Statewide Longitudinal Trends in Transmitted HIV-1 Drug Resistance in Rhode Island, USA. (7th December 2021) - Novitsky, Vlad; Steingrimsson, Jon; Gillani, Fizza S; Howison, Mark; Aung, Su; Solomon, Matthew; Won, Cindy Y; Brotherton, Amy; Shah, Rajeev; Dunn, Casey; Fulton, John; Bertrand, Thomas; et al.
Abstract: Background: HIV-1 transmitted drug resistance (TDR) remains a global challenge that can impact care, yet its comprehensive assessment is limited and heterogenous. We longitudinally characterized statewide TDR in Rhode Island. Methods: Demographic and clinical data from treatment-naïve individuals were linked to protease, reverse transcriptase, and integrase sequences routinely obtained over 2004–2020. TDR extent, trends, impact on first-line regimens, and association with transmission networks were assessed using the Stanford Database, Mann-Kendall statistic, and phylogenetic tools. Results: In 1123 individuals, TDR to any antiretroviral increased from 8% (2004) to 26% (2020), driven by non-nucleotide reverse transcriptase inhibitor (NNRTI; 5%–18%) and, to a lesser extent, nucleotide reverse transcriptase inhibitor (NRTI; 2%–8%) TDR. Dual- and triple-class TDR rates were low, and major integrase strand transfer inhibitor resistance was absent. Predicted intermediate to high resistance was in 77% of those with TDR, with differential suppression patterns. Among all individuals, 34% were in molecular clusters, some only with members with TDR who shared mutations. Among clustered individuals, people with TDR were more likely in small clusters. Conclusions: In a unique (statewide) assessment over 2004–2020, TDR increased; this was primarily, but not solely, driven by NNRTIs, impacting antiretroviral regimens. Limited TDR to multiclass regimens and pre-exposure prophylaxis are encouraging; however, surveillance and its integration with molecular epidemiology should continue in order to potentially improve care and prevention interventions.